Fundamentals of turbomachines - Dick, Erik; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2015)
This book explores the working principles of all kinds of turbomachines. The same theoretical framework is used to analyse the different machine types. Fundamentals are first presented and theoretical concepts are then elaborated for particular machine types, starting with the simplest ones.For each machine type, the author strikes a balance between building basic understanding and exploring knowledge of practical aspects. Readers are invited through challenging exercises to consider how the theory applies to particular cases and how it can be generalised. The book is primarily meant as a course book. It teaches fundamentals and explores applications. It will appeal to senior undergraduate and graduate students in mechanical engineering and to professional engineers seeking to understand the operation of turbomachines. Readers will gain a fundamental understanding of turbomachines. They will also be able to make a reasoned choice of turbomachine for a particular application and to understand its operation. Basic design of the simplest turbomachines as a centrifugal fan, an axial steam turbine or a centrifugal pump, is also possible using the topics covered in the book.
1. Working Principles -- 2. Basic Components -- 3. Fans -- 4. Compressible Fluids -- 5. Performance Measurement -- 6. Steam Turbines -- 7. Dynamic Similitude -- 8. Pumps -- 9. Hydraulic Turbines -- 10. Wind Turbines -- 11. Power Gas Turbines -- 12. Thrust Gas Turbines -- 13. Axial Compressors -- 14. Radial Compressors -- 15. Axial and Radial Turbines for Gases -- References -- Index.
Electronic reproduction.
Keywords: Turbomachines; Turbines; Electronic books